2022
DOI: 10.3390/ijms231911970
|View full text |Cite
|
Sign up to set email alerts
|

Gene Networks Involved in Plant Heat Stress Response and Tolerance

Abstract: Global warming is an environmental problem that cannot be ignored. High temperatures seriously affect the normal growth and development of plants, and threaten the development of agriculture and the distribution and survival of species at risk. Plants have evolved complex but efficient mechanisms for sensing and responding to high temperatures, which involve the activation of numerous functional proteins, regulatory proteins, and non-coding RNAs. These mechanisms consist of large regulatory networks that regul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 104 publications
0
5
0
Order By: Relevance
“…To test this hypothesis, we analyzed the transcriptional dynamics of several HSR genes belonging to Cluster 2 at 24 h, 48 h, 4 days, and 7 days after being exposed to the control temperature, 21 °C, and 29 °C in both varieties. Thus, we monitored the pattern of expression of four well-known core HSR genes, including the small heat-shock protein, BnHSP17.6 ; the ATP-dependent chaperone of the HSP70 family, BnHSP70 ; the mitochondrion-localized small heat-shock protein, BnHSP23.6M ; and the HS-induced galactinol synthase, BnGolS1 , by qPCR ( Figure 7 C) [ 42 , 43 ]. As expected, we found that all these genes started to increase their expression at 24 h after 29 °C exposure.…”
Section: Resultsmentioning
confidence: 99%
“…To test this hypothesis, we analyzed the transcriptional dynamics of several HSR genes belonging to Cluster 2 at 24 h, 48 h, 4 days, and 7 days after being exposed to the control temperature, 21 °C, and 29 °C in both varieties. Thus, we monitored the pattern of expression of four well-known core HSR genes, including the small heat-shock protein, BnHSP17.6 ; the ATP-dependent chaperone of the HSP70 family, BnHSP70 ; the mitochondrion-localized small heat-shock protein, BnHSP23.6M ; and the HS-induced galactinol synthase, BnGolS1 , by qPCR ( Figure 7 C) [ 42 , 43 ]. As expected, we found that all these genes started to increase their expression at 24 h after 29 °C exposure.…”
Section: Resultsmentioning
confidence: 99%
“…It renders plants more susceptible to stress by boosting ROS levels at the cellular level. (Huang et al, 2022). In vitro ubiquitination assays were performed in rice plants, and mediated ubiquitination was validated using the Ni-NTA puri cation technique (Kim).…”
Section: Discussionmentioning
confidence: 99%
“…High temperature is one of the major abiotic stresses that limits plant growth and production. In response to high temperature signals, plants can activate diverse pathways encompassing phytohormone signal transduction (e.g., ABA, SA, JA), transcriptional regulation (e.g., HSF, NAC, MYB, bZIP, WRKY), and epigenetic regulation (Huang et al, 2022). Among these mechanisms, the HSF ‐ HSP pathway has been extensively investigated (Ohama et al, 2017; Zhou et al, 2022).…”
Section: Discussionmentioning
confidence: 99%